1989
DOI: 10.1111/j.1532-5415.1989.tb05684.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age and Blood Pressure on the Hemodynamic and Humoral Response to Head‐Up Tilt

Abstract: It has been reported that postural hypotension in the elderly is common. However, these studies included institutionalized and more or less disabled persons. Furthermore, postural hypotension may be related to baseline blood pressure. In this study, the influence of age and blood pressure on the hemodynamic and plasma catecholamine responses to orthostatic stress was investigated in young and old normotensive and hypertensive healthy subjects. In normotensive and hypertensive elderly persons, the percentage bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…In contrast, when cardiovascular medications were given, systolic BP remained stable during the 10‐minute period of standing, whereas when no medication was administered, there was an initial decline followed by an increase in systolic BP. This difference may be explained by a small but nonsignificant difference in baseline BP inasmuch as it has been demonstrated that higher supine BPs are associated with greater declines after standing 15,20,26 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when cardiovascular medications were given, systolic BP remained stable during the 10‐minute period of standing, whereas when no medication was administered, there was an initial decline followed by an increase in systolic BP. This difference may be explained by a small but nonsignificant difference in baseline BP inasmuch as it has been demonstrated that higher supine BPs are associated with greater declines after standing 15,20,26 …”
Section: Discussionmentioning
confidence: 99%
“…Since aging has been reported to be associated with decreases in leg venous compliance [21,23], the exacerbated ABP instability in the older subjects is probably not due to greater LBNPinduced peripheral venous pooling [31]. On the other hand, it has been demonstrated that increases in blood plasma norepinephrine concentrations are not significantly different between older and younger healthy subjects in response to either head-up tilt [6,11] or LBNP [34], despite the finding that muscle sympathetic nerve responses to LBNP appear to be augmented in older subjects [3]. However, it has been established that aging is associated with a decrease in ·-adrenoceptor sensitivity [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…In 40–50% of elderly patients, heart failure is caused by left ventricular diastolic dysfunction as a result of increased interstitial connective tissue depositions, decreased cardiovascular compliance and compensatory left ventricular hypertrophy (Rich, 1997; Tresch, 1997). Because standing results in a decreased pre‐load by a reduced venous return and in an increased afterload by higher peripheral resistance, diminished ventricular function may increase the risk of orthostatic cerebral symptoms (Levine et al , 1983; Jansen et al , 1989; Wei, 1992; Raiha et al , 1995; van Kraaij et al , 2000).…”
Section: Introductionmentioning
confidence: 99%